Inclusive Education: Typically Developing Student's Sentiments, Attitudes, and Concerns - Rahmi, Iftita; Praptiwi, Rahma Nur; Rahmawati, Anita (KnE Social Sciences, 2024)
Politeknik Negeri Jakarta (PNJ) is a prominent higher education institution in Indonesia that extends its educational services to students with special educational needs (SEN). However, the existing educational practices at PNJ exhibit a partial inclusivity model, whereby SEN students are segregated into separate classes and study programs distinct from their typically developing (TD) peers. The sentiments, attitudes, and concerns of TD students play a pivotal role in the overall success of inclusive education (IE) initiatives. This study seeks to investigate the above regarding IE within the context of PNJ. The study encompassed a sample of 400 students from PNJ, employing a quantitative methodology with a descriptive and correlational non-experimental approach. The results unveiled that a majority of the participants held a moderate level of sentiments, attitudes, and concerns toward inclusive education. Notably, factors such as direct contact with persons with disabilities (PwD), knowledge about PwD, and confidence levels in interacting with them emerged as influential determinants in shaping sentiments, attitudes, and concerns related to IE. This research offers valuable insights into the perceptions of TD students concerning IE at PNJ, which can inform policy recommendations aimed at enhancing educational provisions for SEN students. The findings underscore the importance of fostering a more inclusive and supportive educational environment, promoting positive attitudes, and addressing concerns to facilitate the successful implementation of inclusive education practices within the institution. Keywords: inclusive education, sentiments, attitudes, concerns, typically developing students, special educational needs students